Not all pycnodysostosis‐related mutants of human cathepsin K are inactive – crystal structure and biochemical studies of an active mutant I249T. (26th September 2018) - Roy, Sumana; Das Chakraborty, Sudeshna; Biswas, Sampa
Abstract : Human cathepsin K (CTSK) is a collagenolytic lysosomal cysteine protease that plays an important role in bone turnover. Mutation in CTSK gene is associated with loss of collagenolytic activity of CTSK leading to an autosomal recessive bone disorder called pycnodysostosis. Although a number of pycnodysostotic missense mutations have been reported, underlying mechanism of the disease is not clear. In this study, we investigated in vitro six recombinant pycnodysostosis‐related mutants of human CTSK (G79E, I249T, G243E, G303E, G319C and Q187P). While all the mutants, like wild‐type, show similar high levels of expression in Escherichia coli, four of them (G79E, G303E, G319C and Q187P) are inactive, unstable and spontaneously degrade during purification process. In contrast, proteolytic/collagenolytic activity, zymogen activation kinetics and stability of G243E and I249T mutants are nominally affected. Crystal structure of I249T at 1.92 Å resolution shows that the mutation in R‐domain causes conformational changes of a surface loop in the L‐domain although the catalytic cleft remains unaltered. Molecular simulation, normal mode analysis and fluorescence lifetime measurement eliminated the possibility that the change in L‐domain surface loop orientation is a crystallization artefact. CD‐based thermal melting profile indicates that stability of I249T is significantly higher than wild‐type. Our studies first time reports that pycnodysostosis‐related mutations do not always lead to complete loss of general proteolytic activity or specific collagenolytic activity of CTSK. The first crystal structure of a pycnodysostotic mutant (I249T) provides critical information that may pave new avenues towards understanding the disease at molecular level. Database: The atomic co‐ordinates and structure factors for I249T mutant of human CTSK (codes 5Z5O) have been deposited in the Protein Data Bank (http://wwpdb.org/ ) Abstract : Human lysosomal cathepsin K (CTSK) protease plays an important role in bone remodelling and is responsible for the bone disorder, pycnodysostosis. Here, we characterize the CTSK pycnodysostosis‐related mutant I249T and identify conformational changes away from its active site; thus, loss of protease activity does not always lead to this disease.